Fossil billfish (Xiphioidei) from the Eocene of Hampden, North Otago, New Zealand - Seabourne Rust; Morne Wium; Rodrigo A. Otero; Marianna Terezow (Gondwana Research, 2026)

Relative size predicts competitive outcome through 2 million years - Lee Hsiang Liow; Emanuela Di Martino; Malgorzata Krzeminska; Mali Ramsfjell; Seabourne Rust; Paul D. Taylor; Kjetil L. Voje (Ecology Letters, 2017)
Competition is an important biotic interaction that influences survival and reproduction. While competition on ecological timescales has received great attention, little is known about competition on evolutionary timescales. Do competitive abilities change over hundreds of thousands to millions of years? Can we predict competitive outcomes using phenotypic traits? How much do traits that confer competitive advantage and competitive outcomes change? Here we show, using communities of encrusting marine bryozoans spanning more than 2 million years, that size is a significant determinant of overgrowth outcomes: colonies with larger zooids tend to overgrow colonies with smaller zooids. We also detected temporally coordinated changes in average zooid sizes, suggesting that different species responded to a common external driver. Although species‐specific average zooid sizes change over evolutionary timescales, species‐specific competitive abilities seem relatively stable, suggesting that traits other than zooid size also control overgrowth outcomes and/or that evolutionary constraints are involved.